2010
DOI: 10.1038/ajg.2010.1
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Resection for Barrett's High-Grade Dysplasia and Early Esophageal Adenocarcinoma: An Essential Staging Procedure With Long-Term Therapeutic Benefit

Abstract: ER alters histological grade or local T stage in 48% of patients and dramatically reduces esophagectomy rates by providing safe and effective therapy. ER has a high success rate (94%) for CBE in short segment Barrett's esophagus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
123
0
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(138 citation statements)
references
References 40 publications
7
123
0
8
Order By: Relevance
“…Adequate training and expertise in the recognition of mucosal lesions that may harbor neoplasia is critical in order to target such endoscopic abnormalities with EMR. It is well known that EMR of mucosal abnormalities alters the pathologic stage in ∼ 50% of patients with clear management implications ( 113,192 ). Furthermore, all randomized clinical trials of radiofrequency ablation required endoscopic resection of mucosal abnormalities before application of radiofrequency ablation.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Adequate training and expertise in the recognition of mucosal lesions that may harbor neoplasia is critical in order to target such endoscopic abnormalities with EMR. It is well known that EMR of mucosal abnormalities alters the pathologic stage in ∼ 50% of patients with clear management implications ( 113,192 ). Furthermore, all randomized clinical trials of radiofrequency ablation required endoscopic resection of mucosal abnormalities before application of radiofrequency ablation.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…On the other hand, Pech et al ( 16 ) reported that the rate of metachronous recurrence was 21.5 % and Moss et al ( 40 ) reported a rate of 11 % in Western countries. Th is recurrence rate is higher than that in our study.…”
Section: Esophagusmentioning
confidence: 99%
“…1 and 2). furthermore, different studies have shown that staging by EMR can modify the previous biopsy diagnosis in up to 48 % of cases (93,102,103), which can dramatically change the clinical management of these patients, some of whom would be no longer suitable for endoscopic treatment due to histological evidence of submucosal invasion. Tumor staging using EMR pathology assessment is accurate when compared with surgical pathology, as shown in a study in 25 patients with HGD, IMC in Barrett's esophagus, where there was perfect agreement in T staging after EMR and esophagectomy (104).…”
Section: Endoscopic Mucosal Resection (Emr)mentioning
confidence: 99%